2020
DOI: 10.1136/bmjopen-2019-035876
|View full text |Cite
|
Sign up to set email alerts
|

Health profile of residents of retirement villages in Auckland, New Zealand: findings from a cross-sectional survey with health assessment

Abstract: ObjectivesRetirement villages (RV) have expanded rapidly, now housing perhaps one in eight people aged 75+ years in New Zealand. Health service initiatives might better support residents and offer cost advantages, but little is known of resident demographics, health status or needs. This study describes village residents—their demographics, socio-behavioural and health status—noting differences between participants who volunteered and those who were sampled.DesignCross-sectional study of village residents. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
42
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 14 publications
(48 citation statements)
references
References 29 publications
5
42
0
Order By: Relevance
“…Mean FI in that study (0.27) was higher than in the current study; however, this is unsurprising given participants in the Canterbury study were specifically assessed for access to government‐funded community supports or residential care admission. In the current study, 34% of participants were receiving household assistance and 10% personal care supports 23 . Results from the current study may therefore be closer to the prevalence of frailty in older adults in the wider community in NZ.…”
Section: Discussionsupporting
confidence: 50%
“…Mean FI in that study (0.27) was higher than in the current study; however, this is unsurprising given participants in the Canterbury study were specifically assessed for access to government‐funded community supports or residential care admission. In the current study, 34% of participants were receiving household assistance and 10% personal care supports 23 . Results from the current study may therefore be closer to the prevalence of frailty in older adults in the wider community in NZ.…”
Section: Discussionsupporting
confidence: 50%
“…With regard to the structure of examined groups, our results confirmed a larger participation of women and younger people among volunteers and this finding was consistent with previous observations in this regard [1,14]. This finding was also in line with the results of other cross-sectional studies concerned with different goals of public health, in which females engage more frequently [14][15][16][17]. Importantly, within our study and compared with randomly selected subjects, the volunteers had a significantly higher percentage of positive IgG test results, probably due to their more frequent contact with the SARS-CoV-2 coronavirus.…”
Section: Discussionsupporting
confidence: 92%
“…As mentioned above, the volunteer bias shown in our study affected all pertinent aspects of research, starting with the baseline description of the subjects. Such an observation was similar to the results of the New Zealand study in which volunteers and sampled subjects differed significantly, mainly in socio-behavioral respects [ 15 ]. In another current publication, the authors concluded that depending on the sampling location and time, people who are present to be sampled may be at a higher or lower risk of COVID-19 than the average risk in the source population [ 18 ].…”
Section: Discussionsupporting
confidence: 87%
“…RVs offer a range of facilities and supports, varying from stand-alone secure units, to home/personal care and healthcare supports, with many in NZ also having long-term residential care (LTC) amenities, such as nursing home/private hospital, dementia and psychogeriatric care, on-site. The perceived availability of health and care supports is one of several deciding factors for relocation to RVs identified in those financially able to choose RV lifestyles [ 2 , 3 ]. Our earlier research suggests many residing in RVs live with considerable unmet health needs and symptoms [ 2 , 4 ], and may represent those with greater dependency than their community-dwelling peers.…”
Section: Introductionmentioning
confidence: 99%
“…The perceived availability of health and care supports is one of several deciding factors for relocation to RVs identified in those financially able to choose RV lifestyles [ 2 , 3 ]. Our earlier research suggests many residing in RVs live with considerable unmet health needs and symptoms [ 2 , 4 ], and may represent those with greater dependency than their community-dwelling peers. Consistent with this, some frail older adults perceive RV living as an alternative to LTC [ 5 ].…”
Section: Introductionmentioning
confidence: 99%